2015
DOI: 10.1017/s0033291715002603
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress and the anxious brain: evidence for a neural mechanism linking childhood emotional maltreatment to anxiety in adulthood

Abstract: Background Childhood emotional maltreatment (CEM) increases likelihood of developing an anxiety disorder in adulthood, but the neural processes underlying conferment of this risk have not been established. Here, we test the potential for neuroimaging the adult brain to inform understanding of the mechanism linking CEM to adult anxiety symptoms. Methods One hundred eighty-two adults (148 females, 34 males) with a normal-to-clinical range of anxiety symptoms underwent structural and functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 96 publications
1
40
2
Order By: Relevance
“…Given the requirement of NMDA receptor-mediated activity within PFC circuits during cognitive tasks (Arnsten & Rubia, 2012), this would presumably result in less recruitment of the PFC as required for effective top-down control. In support of this, reduced neural activity within the PFC when performing a variety of executive function tasks is commonly observed in human adults reporting experience of chronic juvenile stressors (Table 2; e.g., Casement et al, 2015; Fonzo et al, 2016; Philip et al, 2013b; 2016). However, chronic juvenile stress is also associated with increased brain-derived neurotrophic factor (BDNF) in the PFC of adult rats (Table 1; Han et al, 2011b; Meng et al, 2011; Shao et al, 2013), which is surprising given that reduced gray matter, reduced dendritic length or elaboration, and reduced plasticity are often observed in the adult PFC following juvenile stress in both humans and animal models (Tables 1 & 2).…”
Section: Impact Of Chronic Juvenile Stress On Prefrontal Cortex Anmentioning
confidence: 74%
“…Given the requirement of NMDA receptor-mediated activity within PFC circuits during cognitive tasks (Arnsten & Rubia, 2012), this would presumably result in less recruitment of the PFC as required for effective top-down control. In support of this, reduced neural activity within the PFC when performing a variety of executive function tasks is commonly observed in human adults reporting experience of chronic juvenile stressors (Table 2; e.g., Casement et al, 2015; Fonzo et al, 2016; Philip et al, 2013b; 2016). However, chronic juvenile stress is also associated with increased brain-derived neurotrophic factor (BDNF) in the PFC of adult rats (Table 1; Han et al, 2011b; Meng et al, 2011; Shao et al, 2013), which is surprising given that reduced gray matter, reduced dendritic length or elaboration, and reduced plasticity are often observed in the adult PFC following juvenile stress in both humans and animal models (Tables 1 & 2).…”
Section: Impact Of Chronic Juvenile Stress On Prefrontal Cortex Anmentioning
confidence: 74%
“…This view on their childhood would be more confronting than to simply acknowledge that their parents did not show interest in setting rules or monitoring their social contacts. However, even though the omission of parental care, control and monitoring does not provoke – in general – dramatic symptoms or recollections, studies showed that an emotionally abusive or neglectful parenting style deeply affected the self-representations [56] or the cerebral activation patterns of the individual later in life [57]. For example, students who had experienced and evaluated experiences of emotional abuse or neglect were shown to have developed profoundly anchored cognitive schemas of vulnerability and the impact of these internalizations on observed outcomes such as anxiety and depression might be even stronger, than the direct effects of the underlying events themselves [58].…”
Section: Discussionmentioning
confidence: 99%
“…Early life stress has been linked to long term functional and structural changes to the amygdala, hippocampus, and the Hypothalamic-Pituitary-Adrenal axis [14,56,57]. The amygdala processes emotional stimuli and dysfunction in this brain region is associated with deficits in emotion regulation, anxiety and depression.…”
Section: The Role Of Affective Functioningmentioning
confidence: 99%